ANALISIS FAKTOR-FAKTOR PENYEBAB GOLPUT PILKADA DI KOTA MEDAN - Rizki Bastanta B. Manalu (Journal Recht (JR), 2022)
The implementation of elections that took place in Indonesia, namely legislative elections in presidential elections and regional elections, often occurs the phenomenon of white voters or often called abstentions. In the city of Medan, the abstentions occurred during the mayoral election in 2020. So this problem is of interest to researchers to analyze this. Thus, the purpose of this research is to examine and analyze the factors that cause abstentions from the elections in Medan City in 2020. The theoretical approach used is the theory of electoral behavior from Albert Bandura. The method used in this study is a qualitative descriptive approach used in this research to see facts and events systematically and accurately. As for the sources of data in this study, the people who did not use their right to vote during the local elections took place as well as the regional election organizers, namely the KPU of Medan City. Data was collected by interview, observation and documentation techniques. The research uses qualitative analysis, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that the factors that cause abstentions in the local elections in Medan City can be seen from internal factors and external factors. Internal factors such as distrust of candidates, the notion that elections are not important, employment factors. While external factors such as socialization and campaign factors, administrative factors, ideological factors.